2013
DOI: 10.1097/mcp.0b013e3283659da5
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and diabetes

Abstract: OSA is associated with insulin resistance and β-cell dysfunction independent of obesity. OSA is associated with HbA1c and vascular complications in patients with T2D. CPAP might improve insulin resistance and glycaemic measures. Lifestyle intervention has a significant impact on AHI in patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 116 publications
0
64
1
Order By: Relevance
“…28,[30][31][32] In General Population Studies Several cross-sectional studies showed an association between OSA and IR but some studies did not show such an association. 7,10,11 Obesity is obviously a major confounder but the association between OSA and IR was also found in lean individuals, suggesting that the relationship is independent of obesity. 33,34 One study examined the effect of OSA on IR longitudinally; over 11-year follow-up OSA, AHI, oxygen desaturation index (ODI) and minimal oxygen saturations overnight were independently associated with IR after adjustment for age, baseline BMI, hypertension, BMI change over follow-up and CPAP treatment.…”
Section: Obstructive Sleep Apnoea and Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…28,[30][31][32] In General Population Studies Several cross-sectional studies showed an association between OSA and IR but some studies did not show such an association. 7,10,11 Obesity is obviously a major confounder but the association between OSA and IR was also found in lean individuals, suggesting that the relationship is independent of obesity. 33,34 One study examined the effect of OSA on IR longitudinally; over 11-year follow-up OSA, AHI, oxygen desaturation index (ODI) and minimal oxygen saturations overnight were independently associated with IR after adjustment for age, baseline BMI, hypertension, BMI change over follow-up and CPAP treatment.…”
Section: Obstructive Sleep Apnoea and Insulin Resistancementioning
confidence: 99%
“…7,8 OSA is characterised by upper airway instability during sleep that results in recurrent upper airway obstruction resulting in either complete or partial cessation of airflow (i.e. apnoea and hypopnoea, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing prevalence of obesity and the increasing population body mass index has created major public health challenges [11] . Obstructive sleep apnea has been independently linked with hypertension, atrial fibrillation, cardiac disease, worsening of diabetes, insulin resistance, peri-operative and postoperative complications and coronary artery disease (CAD), to name the few [12][13][14][15][16] .…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%